A folded filter element based on PTFE modified separation membrane and preparation method thereof
By doping PTFE resin with specific materials and performing multi-layer membrane treatment, a pleated filter element based on PTFE-modified separation membrane was prepared, which solved the problem of short life and filtration problems of hydrophilic PTFE-modified separation membrane during use. solve the problem of poor performance and achieve longer service life and higher filtration efficiency.
Patent Information
- Application Number
- CN202411376884.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2023-10-20
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-09-30
AI Technical Summary
The existing hydrophilic PTFE modified separation membranes have short life, poor filtration effect and "water bonding" during use, resulting in a decrease in inter-membrane constraints and filtration capacity.
By mixed with methalum, water, 8-hydroxylin, acrylamide and other materials in PTFE resin, a modified separation film is formed, and the multi-layer membrane roller composite and thermal pressure treatment, combined with organic solvent soaking and stacking materials composite , Prepare a folding filter element based on the PTFE modified separation membrane.
It eliminates the inter-membrane restriction phenomenon, extends the service life of the filter element, ensures the filtration rate and effect, avoids the occurrence of "water adhesion" phenomenon, and improves the antibacterial performance of the filter element.
Smart Images

Figure CN118874241B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of filter materials, and in particular relates to a folded filter element based on a PTFE modified separation membrane and a preparation method thereof. Background Art
[0002] Filter devices and different filter media are widely used in the liquid bacterial filtration, particle filtration and other liquid purification applications in the pharmaceutical fermentation, bioengineering, food and beverage, modern chemical industry, electronics industry, environmental protection and other industries. In the field of microfiltration, pleated filter elements are commonly used in filter devices. The filter media of pleated filter elements are made of polymer materials, but the chemical compatibility, weather resistance and temperature resistance of different polymer materials vary greatly.
[0003] The commonly used polytetrafluoroethylene microporous filter membrane has excellent chemical compatibility and high temperature resistance, and can withstand more stringent filtration systems and application environments. However, the strong hydrophobicity of polytetrafluoroethylene greatly limits the application of this filter material in the finned pleated filter element of the cylindrical filter.
[0004] At present, hydrophilic modification of PTFE is a relatively common and common operation. However, when hydrophilic PTFE is used in folded filter elements, there is a serious problem of fin adhesion, that is, after a period of use, adjacent fins will be close to each other under the action of intermolecular forces, until they are completely "adhered", resulting in some of them being completely folded and some flattened, which in turn produces "inter-membrane constraints", greatly reducing the effective filtration area, and the filtration effect of the PTFE filter element is significantly reduced after being over-stretched, requiring frequent replacement and making it difficult to maintain the filtration capacity. Summary of the invention
[0005] In order to solve the problems of short service life, poor filtering effect, obvious "water adhesion" phenomenon and membrane restriction in the use of existing hydrophilic PTFE modified separation membranes, the present invention provides a foldable filter element based on PTFE modified separation membrane and a preparation method of the filter element.
[0006] The purpose of the present invention is: 1. To eliminate the phenomenon of membrane restriction occurring during the actual use of PTFE modified separation membrane.
[0007] 2. Extend the service life of the pleated filter element.
[0008] 3. Ensure the filtration rate and filtration effect of the filter element.
[0009] To achieve the above objectives, the present invention adopts the following technical solutions.
[0010] A method for preparing a foldable filter element based on a PTFE modified separation membrane, the method comprising: (1) taking a PTFE resin, heating and stirring it to melt it into a fluid, and then putting it on a screen for molding; during the molding process, after the material temperature drops to 105-115°C, fibers, water, an antibacterial agent, acrylamide and an initiator are evenly added to obtain a PTFE base membrane.
[0011] (2) The PTFE base membrane is stretched, and the multilayer membrane is roll-laminated and then hot-pressed to obtain a PTFE separation membrane.
[0012] (3) The PTFE separation membrane is immersed in an organic solvent to obtain a PTFE modified separation membrane.
[0013] (4) The soaked PTFE modified separation membrane is stacked with stacking materials in sequence to prepare a foldable filter element based on the PTFE modified separation membrane.
[0014] Preferably, the web forming in step (1) is dried to form a film under the conditions of an ambient temperature of 20-60°C and an air flow rate of 25-30 km / h, and the film thickness is controlled to be 0.5-2.0 mm and the flatness is ≤0.1 mm.
[0015] Preferably, the fiber in step (1) is chitin fiber; the antibacterial agent in step (1) is 8-hydroxyquinoline; the fiber, water and antibacterial agent in step (1) are mixed in a ratio of 2: (0.3-0.7): (0.2-0.5), and the amount added after mixing is 40-60 wt% of the PTFE value.
[0016] Preferably, in step (1), the amount of acrylamide added is 5 to 10 wt% of the mass of PTFE; and the initiator in step (1) is dibenzoyl peroxide, and the amount added is 1 to 3 wt% of the mass of acrylamide.
[0017] Preferably, the stretching in step (2) is performed by stretching the PTFE base film at 200-300° C., and the stretching ratio is controlled to be 150-300% during the stretching process.
[0018] Preferably, during the roll-compounding of the multilayer membrane in step (2), the total thickness of the multilayer membrane when stacked is controlled to be 115-120% of the target thickness of the PTFE modified separation membrane, and then the multilayer membrane is rolled to 110-115% of the target thickness of the PTFE modified separation membrane; the hot pressing treatment in step (2) is performed at 110-115°C to heat-press the membrane to the target thickness of the PTFE modified separation membrane.
[0019] Preferably, the organic solvent in step (3) is a mixture of aluminum triethylphosphate and ammonia water, wherein the mass ratio of aluminum triethylphosphate to ammonia water is 1:(4-6), and the amount of organic solvent added is 200-500%VOL of the volume of the PTFE base membrane; and the concentration of ammonia water is 25-28 wt%.
[0020] Preferably, the stacking material in step (4) comprises long-fiber non-woven fabric, short-fiber non-woven fabric and a planar guide net; and the composite stacking in step (4) is stacked in the order of long-fiber non-woven fabric-short-fiber non-woven fabric-PTFE modified separation membrane-planar guide net, and then folded into fins to obtain a folded filter element.
[0021] The invention discloses a folded filter element based on a PTFE modified separation membrane.
[0022] Preferably, the folded filter element is wrapped around and fixed on the circumferential outer surface of the inner support tube of the cylindrical filter structure, and then an outer support tube is sleeved on the outer surface of the folded filter element.
[0023] The two sides of the folded filter element are controlled so that the long-fiber non-woven fabric is located on the upstream side of the fluid flow path, and the planar flow guide net is located on the downstream side of the fluid flow path.
[0024] The core of the technical solution of the present invention is to enhance the performance of the separation membrane by doping with other fiber materials and eliminate the restriction phenomenon between the PTFE modified separation membranes.
[0025] In actual application, PTFE is a membrane separation material with excellent comprehensive performance, with excellent chemical stability, heat resistance, cold resistance and chemical corrosion resistance, and at the same time, it also has good electrical insulation, low surface tension and low friction coefficient, non-flammability, atmospheric aging resistance, high and low temperature adaptability and high mechanical properties, and has broad application prospects in the field of membrane separation. However, due to the low surface energy and strong hydrophobicity of such membrane materials, when treating the aqueous phase separation system, the mass transfer driving force of the fluid through the membrane is high, the energy consumption is large, and the water flux is low; in addition, the hydrophobic membrane surface is very easy to adsorb impurities such as organic matter and protein, resulting in concentration polarization, causing the membrane to be seriously polluted, thereby causing a sharp drop in flux. These shortcomings restrict the further promotion and application of PTFE, so the present invention first performs a unique hydrophilic modification on the PTFE membrane.
[0026] In the technical solution of the present invention, the PTFE membrane is connected with carboxyl and hydroxyl hydrophilic groups, so that a large number of hydrogen bonds exist on the surface of the separation membrane, which can provide hydrogen atoms for the formation of hydrogen bonds. At the same time, the lone pair of electrons on the oxygen atoms in the polar functional groups can accept hydrogen atoms provided by other molecules, and can form hydrogen bonds with the lone pair of electrons and hydrogen ions on the oxygen atoms between water molecules respectively. Since the PTFE membrane with the external groups forms hydrogen bonds with water molecules with similar structures, the affinity of the PTFE membrane with water is improved, thereby completing the hydrophilic modification of the PTFE membrane.
[0027] In the PTFE modified separation membrane of the present invention, chitin is adsorbed on the surface of the PTFE resin to produce steric hindrance, inhibiting the aggregation between particles, and a small amount of polyacrylamide is evenly arranged in the membrane material, which can be used as a support for holes in the resin modification process, and provides a spatial structure for the enrichment of metal ions. The cooperation of the two structures enables the PTFE modified separation membrane of the present invention to produce a relatively excellent internal molecular manufacturing effect while forming hydrophilicity, and can avoid the occurrence of the "water bonding" phenomenon, especially in the filtering process, the filter element of the present invention is mainly filtered and enriched for metal ion impurities in industrial wastewater, and metal ions are usually enriched on the surface of the filter element and enhance the occurrence of the "water bonding" phenomenon, and the present invention forms a microscopic molecular support structure to support the structure of the PTFE modified separation membrane while enriching the metal ions inside, so that the metal ions will not only not be enriched on the surface to enhance the "water bonding" effect to produce inter-membrane constraints, but will enhance the intramolecular support effect, so that the structure of the PTFE modified separation membrane of the present invention is more stable and has a longer service life.
[0028] In addition, when conventional PTFE modified separation membranes are stacked in multiple layers, another form of inter-membrane restriction also occurs, which causes a large amount of filtrate to accumulate at the stacking interface of the PTFE separation membrane, resulting in a large amount of impurities, causing the flow rate of the filter element to drop rapidly, making it difficult to effectively filter. At the same time, the enrichment of impurities may cause the filter element to deform to a certain extent, further reducing the filtering effect.
[0029] Through multiple modifications, the service life of the pleated filter element is extended, the inter-membrane restriction effect is suppressed, and the filtration rate and filtration effect of the filter element are improved.
[0030] In the technical solution of the present invention, acrylamide and initiator can be polymerized under normal temperature to form polyacrylamide, and a large amount of heat is released at the same time. Under the catalysis of thermal energy, 8-hydroxyquinoline is introduced into the tetrafluoroethylene resin skeleton to form an 8-hydroxyquinoline chelate resin with special complexing ability. This resin has a strong adsorption effect on heavy metal ions such as chromium, nickel, and zinc in the environment. In the immersion of organic solvents, the chelate resin can form a framework structure composed of metallic aluminum and organic ligands with aluminum triethyl phosphate. The organic framework structure contains a large amount of aluminum ions with antibacterial effects, which can be slowly released as the organic framework changes to achieve a continuous sterilization effect. After the organic framework changes, a large amount of oxygen free radicals can be induced to sterilize. In an ammonia environment, the hydroxyl groups on the surface of the tetrafluoroethylene resin can react with hydroxide ions, so that the surface of the tetrafluoroethylene resin is negatively charged, and the electrostatic repulsion is used to reduce the probability of tetrafluoroethylene resin particles approaching each other to form precipitation.
[0031] The invention team has found through experiments that in the PTFE separation membrane provided by the present invention, the hydroxyquinoline of the 8-hydroxyquinoline chelating resin with special complexing ability undergoes organic condensation to make the resin pores contain relatively H + The ion concentration is high, presenting a relatively weak acidic condition. Under weak acid, the solubility of heavy metal ions increases. When the resin binds a certain amount of H + After ionization, the special structure of 8-hydroxyquinoline chelating resin increases the H + The exchange capacity with heavy metal ions forms polymers. The multi-coordinated functional groups on the polymers form complexes with metal ions. The atoms on the functional groups react with metal ions to produce coordinated covalent bonds and form chelates with stable structures. This is different from the principle of ion exchange resins to adsorb metal ions. Ion exchange resins use electrostatic effects to bind to metal ions. Therefore, the binding of chelated resins to metal ions is more stable, the binding force is stronger, the specific selectivity is better, and the application is more extensive.
[0032] At the same time, in an ammonia solution, the amino and hydroxyl groups in the molecular chain of chitin can form chemical connections with the hydroxyl groups on the surface of tetrafluoroethylene resin, playing a good role in preventing sedimentation and sagging. Tetrafluoroethylene resin will produce "poisoning" during use. The so-called poisoning means that it will lose its ion exchange function after a period of use. During use, the self-polymerization rate of tetrafluoroethylene is greater than the copolymerization with ethylene. Therefore, in the early stage, the proportion of tetrafluoroethylene units entering is higher, while in the later stage, the tetrafluoroethylene monomer has been basically consumed, and the reaction is mainly the self-polymerization of ethylene. As a result, due to the different internal cross-linking densities, the outside is sparse and the inside is dense. During the use of the resin, larger ions or molecules diffuse into the interior of the resin, and during regeneration, due to the sparse outside and dense inside structure, larger ions or molecules will be stuck between molecules. In the gap, it is not easy to exchange with mobile ions, and eventually lose some functions, causing resin "poisoning". However, when there are larger pore channels inside the resin, the structure of sparse outside and dense inside is avoided, thereby overcoming the poisoning phenomenon. In the technical scheme of the present invention, a small amount of polyacrylamide is evenly arranged in the membrane material, which can be used as a support for the holes in the resin improvement process, providing a spatial structure for the enrichment of metal ions. The resin molecules gradually curl up with the progress of polymerization to form extremely fine molecular spheres. The spheres are entangled with each other through molecular chains to form a cluster of grape-shaped spherical channels, thereby obtaining sufficient gaps and a large specific surface area.
[0033] In addition, the foldable filter element of the present invention is composed of a layer of long fiber non-woven fabric, a layer of fine short fiber non-woven fabric, a layer of PTFE modified separation membrane and a layer of plane guide net, the fine short fiber non-woven fabric is arranged upstream of the filter membrane, the long fiber non-woven fabric is arranged upstream of the fine short fiber non-woven fabric, and the plane guide net is arranged downstream of the filter membrane. The fine short fiber non-woven fabric plays the role of pre-filtration and protection of the filter membrane, increasing the dirt holding capacity of the filter element; the long fiber non-woven fabric enhances the scraping property of the folded layer; the plane guide net reduces the fluid resistance, increases the flow rate of the filter element, and at the same time strengthens the binding force of the PTFE modified separation membrane in the support tube to prevent the fiber from falling off.
[0034] Advantages of the present invention: (1) The folded filter element provided by the present invention eliminates the problem of short filtration capacity and service life caused by the membrane constraints of the PTFE modified separation membrane during actual application.
[0035] (2) The foldable filter element of the present invention has a very excellent filtering effect and internal enrichment ability when used for metal ion filtration, and can avoid the problem of reduced filtering performance due to ion assimilation on the outer surface.
[0036] (3) The present invention uses other fibers in the polytetrafluoroethylene resin to build a spatial structure to ensure the filtration rate and filtration effect of the filter element. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1This is a diagram of the installation structure of the foldable filter element of the present invention.
[0038] Figure 2 for Figure 1 Schematic diagram of the enlarged structure of part A.
[0039] In the figure: 100 inner support cylinder, 200 folded filter element, 201 long fiber non-woven fabric layer, 202 flat guide mesh layer, 300 outer support cylinder. DETAILED DESCRIPTION
[0040] The present invention is further described in detail below in conjunction with specific embodiments. Those of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work should fall within the scope of protection of the present invention.
[0041] Unless otherwise specified, the raw materials used in the examples of the present invention are all commercially available or available to those skilled in the art; unless otherwise specified, the methods used in the examples of the present invention are all methods known to those skilled in the art.
[0042] Example 1: A method for preparing a foldable filter element based on a PTFE modified separation membrane, the specific method is: (1) Take tetrafluoroethylene resin, heat and stir to melt it into a fluid, and then put it on a screen to form a film, and control the thickness to be about 0.6 mm and the flatness ≤ 0.1 mm. During the screen forming process, after the material temperature drops to 105-115°C, a mixture of chitosan, water, and 8-hydroxyquinoline is evenly added at 40 wt% of the resin mass. The chitosan fiber, water, and 8-hydroxyquinoline mixture are evenly mixed in a ratio of 2:0.3:0.2, and at the same time, 5 wt% of acrylamide by weight of the resin and 1 wt% of dibenzoyl oxide by weight of acrylamide are added. After standing and drying in the shade, a PTFE base membrane is obtained.
[0043] (2) The film was stretched at 200 °C with a stretching ratio of 150%. After stretching, the two layers of the film were stacked, rolled to a thickness of 1.1 mm, and then hot-pressed at 110 °C to a thickness of 1.0 mm to obtain a PTFE filter element substrate.
[0044] (3) Mix aluminum triethylphosphate and 25% pure ammonia water in a mass ratio of 1:4 and soak the PTFE filter element in the organic solution at 200% volume of the PTFE filter element substrate for 30 minutes.
[0045] (4) The soaked filter element substrate is stacked in sequence with a layer of long fiber non-woven fabric, a layer of fine short fiber non-woven fabric, a layer of PTFE modified separation membrane and a layer of planar guide mesh to form a filter medium layer, such as Figure 2 As shown in the figure, the long fiber nonwoven fabric 201-short fiber nonwoven fabric-PTFE modified separation membrane-planar flow guide net 202 are stacked in sequence, and then folded into Figure 1 and Figure 2 After the fin structure shown is formed, a folded filter element 200 is obtained, wherein the inner angle α of the fin is less than the outer angle β, and generally the inner angle α is 10-15°, and the outer angle β is 20-25°. For example, in this example and subsequent embodiments and comparative examples, the inner angle α is 12°, and the outer angle β is 22°. In additional supplementary tests, it is found that by controlling the fin structure, the high stability characteristics of the folded filter element 200 of the present invention can be further fully utilized and its performance stability can be effectively ensured. The above angles can form an internal and external pressure difference autonomously under a constant flow rate. In other supplementary experiments, when the inner angle α is greater than the outer angle β, the seepage effect will decrease, the filtration efficiency will decrease, and the filtration effect may be weakened. For example, in one of the supplementary experiments, the inner angle α is 18° and the outer angle β is 15°. In this experiment, the filtration effect is improved by about 6.3-8.1 compared with the sample in this embodiment. The decrease of % is due to the decrease of filtration area and the decrease of filtration efficiency because the inner space ≥ the outer space under the same flow rate cannot effectively form the fluid pressure difference.
[0046] The prepared filter element is assembled into a cylindrical filter and then subjected to the following performance tests. During assembly, the folded filter element is wrapped around the circumferential outer surface of the inner support tube (provided with a hollow flow channel, the same below) of the cylindrical filter structure and fixed, and then an outer support tube (provided with a hollow flow channel, the same below) is sleeved on the outer surface of the folded filter element. The two sides of the folded filter element are controlled so that the long fiber non-woven fabric is on the upstream side of the fluid flow path, and the planar guide net is on the downstream side of the fluid flow path. The specific characterization results are as follows.
[0047] Metal ion removal rate: add dissolved copper sulfate, zinc sulfate, lead sulfate, cadmium hydroxide, ferrous sulfate and ferrous sulfate into pure water, stir to dissolve various components to prepare standard test solution, determine the metal ion content in the test solution at this time as liquid A data, pass the standard test solution through the prepared folded filter element at a flow rate of 8 mm / s for 2 hours, characterize the metal ion content of the filtered solution and record the liquid B data, continue to flow for 2 hours, characterize the metal ion content of the filtered solution and record the liquid C data.
[0048]
[0049] Filter element fatigue test: The above standard test liquid is passed through the prepared folded filter element at a flow rate of 16 mm / s for 24 hours to allow the filter element to reach the maximum pressure difference of the filter element, and the filter element is always kept at the alternating flow rate of the flux, so that the filter element can resist the changes in the filter element structure caused by the alternating changes in its pressure difference caused by flow fluctuations, which is similar to the changes after long-term use. Anti-fatigue test is carried out. After 24 hours, the filter element is taken out and subjected to the same performance test of the above metal ion removal rate. The metal ion content of the solution after 24 hours of filtration is characterized and the liquid D data is recorded.
[0050]
[0051] From the above characterization results, it can be concluded that the folded filter element of the present invention can effectively remove heavy metal pollutants in water bodies, with a copper ion removal rate of more than 99%, a zinc ion removal rate of nearly 99%, a lead ion removal rate of more than 99%, and a cadmium ion removal rate of more than 99%, which can effectively filter and remove heavy metal pollution in water bodies. At the same time, after long-term use, the folded filter element of the present invention can still ensure the effective removal of metal ions in water bodies and extend the service life of the filter element.
[0052] In addition, the antibacterial performance of the PTFE filter element substrate prepared in step (3) after immersion modification was tested by an oscillation method suitable for contact antibacterial materials. Staphylococcus aureus was used as the antibacterial target. The test results showed that the antibacterial rate reached 99%. The antibacterial performance of the folded filter element using the PTFE modified separation membrane prepared in step (4) was also tested. The test results showed that the antibacterial rate reached 97.2%. It can be seen that the PTFE filter element substrate of the present invention has very excellent antibacterial performance, and at the same time, after stacking and folding, it still has good antibacterial properties and can effectively kill common harmful bacteria.
[0053] Example 2: A method for preparing a foldable filter element based on a PTFE modified separation membrane, the specific method is as follows: (1) Take tetrafluoroethylene resin, heat and stir to melt it into a fluid, and then put it on a screen to form a film, and control the thickness to be about 0.6 mm and the flatness ≤ 0.1 mm. During the molding process, after the material temperature drops to 105-115°C, a mixture of chitosan, water, and 8-hydroxyquinoline is evenly added at 50 wt% of the resin mass. The chitosan fiber, water, and 8-hydroxyquinoline mixture are evenly mixed in a ratio of 2:0.5:0.4, and at the same time, 7 wt% of acrylamide by weight of the resin and 2 wt% of dibenzoyl oxide by weight of acrylamide are added, and the mixture is allowed to stand and dry in the shade to obtain a PTFE base membrane.
[0054] (2) The film was stretched at a temperature of 250 °C with a stretching ratio of 200%. After stretching, the two layers of the film were stacked, rolled to a thickness of 1.1 mm, and then hot-pressed at 110 °C to a thickness of 1.0 mm to obtain a PTFE filter element substrate.
[0055] (3) Mix aluminum triethylphosphate and 27% pure ammonia water in a mass ratio of 1:5, and soak the PTFE filter element in the organic solution at 300% volume of the PTFE filter element substrate for 45 minutes.
[0056] (4) The soaked filter element substrate is stacked with a layer of long fiber non-woven fabric, a layer of fine short fiber non-woven fabric, a layer of PTFE modified separation membrane and a layer of planar guide net in sequence to form a filter medium layer. The filter element substrate is stacked in the order of long fiber non-woven fabric-short fiber non-woven fabric-PTFE modified separation membrane-planar guide net, and then folded into fins to obtain a folded filter element.
[0057] The prepared filter element is assembled into a cylindrical filter and then subjected to the following performance tests. During assembly, the folded filter element is wrapped around the circumferential outer surface of the inner support tube of the cylindrical filter structure and fixed, and then an outer support tube is sleeved on the outer surface of the folded filter element. The two sides of the folded filter element are controlled so that the long fiber non-woven fabric is on the upstream side of the fluid flow path, and the planar guide net is on the downstream side of the fluid flow path. The specific characterization results are as follows.
[0058] Metal ion removal rate: add dissolved copper sulfate, zinc sulfate, lead sulfate, cadmium hydroxide, ferrous sulfate and ferrous sulfate into pure water, stir to dissolve various components to prepare standard test solution, determine the metal ion content in the test solution at this time as liquid A data, pass the standard test solution through the prepared folded filter element at a flow rate of 8 mm / s for 2 hours, characterize the metal ion content of the filtered solution and record the liquid B data, continue to flow for 2 hours, characterize the metal ion content of the filtered solution and record the liquid C data.
[0059]
[0060] Filter element fatigue test: The above standard test liquid is passed through the prepared folded filter element at a flow rate of 16 mm / s for 24 hours to allow the filter element to reach the maximum pressure difference of the filter element, and the filter element is always kept at the alternating flow rate of the flux, so that the filter element can resist the changes in the filter element structure caused by the alternating changes in its pressure difference caused by flow fluctuations, which is similar to the changes after long-term use. Anti-fatigue test is carried out. After 24 hours, the filter element is taken out and subjected to the same performance test of the above metal ion removal rate. The metal ion content of the solution after 24 hours of filtration is characterized and the liquid D data is recorded.
[0061]
[0062] Judging from the above characterization results, it also has good deionization ability and long service life.
[0063] In addition, the antibacterial performance of the PTFE filter element substrate obtained by immersion modification in step (3) and the folded filter element of the PTFE modified separation membrane obtained in step (4) were tested respectively. The test was carried out using an oscillation method suitable for contact antibacterial materials. Staphylococcus aureus was used as the antibacterial target. The test results showed that the antibacterial rates reached 99% and 96.7%, respectively.
[0064] Example 3: A method for preparing a foldable filter element based on a PTFE modified separation membrane, the specific method is as follows: (1) Take tetrafluoroethylene resin, heat and stir to melt it into a fluid, and then put it on a screen to form a film, and control the thickness to be about 1.15 mm and the flatness ≤ 0.1 mm. During the molding process, when the material temperature drops to 105-115 °C, a mixture of chitosan, water, and 8-hydroxyquinoline is evenly added at 60 wt% of the resin mass. The chitosan fiber, water, and 8-hydroxyquinoline mixture are evenly mixed in a ratio of 2:0.7:0.5. At the same time, 10 wt% of acrylamide by weight of the resin and 3 wt% of dibenzoyl oxide by weight of acrylamide are added, and the film is allowed to stand and dry in the shade to obtain a PTFE base membrane.
[0065] (2) The film was stretched at a temperature of 300 °C with a stretching ratio of 300%. After stretching, the five layers of the film were stacked, rolled to a thickness of 5.5 mm, and then hot-pressed at 110 °C to a thickness of 5.0 mm to obtain a PTFE filter element substrate.
[0066] (3) Mix aluminum triethylphosphate and 28% pure ammonia water in a mass ratio of 1:6, and soak the PTFE filter element in 500% volume of the above organic solution for 60 minutes.
[0067] (4) The soaked filter element substrate is stacked with a layer of long fiber non-woven fabric, a layer of fine short fiber non-woven fabric, a layer of PTFE modified separation membrane and a layer of planar guide net in sequence to form a filter medium layer. The filter element substrate is stacked in the order of long fiber non-woven fabric-short fiber non-woven fabric-PTFE modified separation membrane-planar guide net, and then folded into fins to obtain a folded filter element.
[0068] The prepared filter element is assembled into a cylindrical filter and then subjected to the following performance tests. During assembly, the folded filter element is wrapped around the circumferential outer surface of the inner support tube of the cylindrical filter structure and fixed, and then an outer support tube is sleeved on the outer surface of the folded filter element. The two sides of the folded filter element are controlled so that the long fiber non-woven fabric is on the upstream side of the fluid flow path, and the planar guide net is on the downstream side of the fluid flow path. The specific characterization results are as follows.
[0069] Metal ion removal rate: add dissolved copper sulfate, zinc sulfate, lead sulfate, cadmium hydroxide, ferrous sulfate and ferrous sulfate into pure water, stir to dissolve various components to prepare standard test solution, determine the metal ion content in the test solution at this time as liquid A data, pass the standard test solution through the prepared folded filter element at a flow rate of 8 mm / s for 2 hours, characterize the metal ion content of the filtered solution and record the liquid B data, continue to flow for 2 hours, characterize the metal ion content of the filtered solution and record the liquid C data.
[0070]
[0071] Filter element fatigue test: The above standard test liquid is passed through the prepared folded filter element at a flow rate of 16 mm / s for 24 hours to allow the filter element to reach the maximum pressure difference of the filter element, and the filter element is always kept at the alternating flow rate of the flux, so that the filter element can resist the changes in the filter element structure caused by the alternating changes in its pressure difference caused by flow fluctuations, which is similar to the changes after long-term use. Anti-fatigue test is carried out. After 24 hours, the filter element is taken out and subjected to the same performance test of the above metal ion removal rate. The metal ion content of the solution after 24 hours of filtration is characterized and the liquid D data is recorded.
[0072]
[0073] Judging from the above characterization results, it also has good deionization ability and long service life.
[0074] Moreover, compared with Example 1 and Example 2, after increasing the number of stacking layers and the total PTFE modified separation membrane thickness, the actual filtering effect and service life are further improved. It can be seen that the folded filter element of the present invention does not produce a significant weakening of the effect after the multi-layer PTFE modified separation membrane is stacked.
[0075] In addition, the antibacterial performance of the PTFE filter element substrate obtained by immersion modification in step (3) and the folded filter element of the PTFE modified separation membrane obtained in step (4) were tested respectively. The oscillation method suitable for contact antibacterial materials was used for the test. Staphylococcus aureus was used as the antibacterial target. The test results showed that the antibacterial rates reached 99% and 97.0%, respectively.
[0076] Comparative Example 1: A method for preparing a foldable filter element based on a PTFE modified separation membrane, wherein the specific preparation method is the same as that of Example 2, except that the organic solvent unique to the present invention is not used to prepare the foldable filter element, and the specific operations are as follows: (1) Take tetrafluoroethylene resin, heat and stir to melt it into a fluid, and then put it on a screen to form a film, and control the thickness to be about 0.6 mm and the flatness to be ≤0.1 mm. During the forming process, after the material temperature drops to 105-115°C, a mixture of chitosan, water, and 8-hydroxyquinoline, which is 50 wt% of the resin mass, is evenly added. The chitosan fiber, water, and 8-hydroxyquinoline mixture are evenly mixed in a ratio of 2:0.5:0.4, and at the same time, 7 wt% of acrylamide by weight of the resin and 2 wt% of dibenzoyl oxide by weight of acrylamide are added, and the mixture is allowed to stand and dry in the shade to obtain a PTFE base membrane.
[0077] (2) The film was stretched at a temperature of 250 °C with a stretching ratio of 200%. After stretching, the two layers of the film were stacked, rolled to a thickness of 1.1 mm, and then hot-pressed at 110 °C to a thickness of 1.0 mm to obtain a PTFE filter element substrate.
[0078] (3) A PTFE filter element substrate is stacked in sequence to form a filter medium layer, which is composed of a layer of long fiber non-woven fabric, a layer of fine short fiber non-woven fabric, a layer of PTFE modified separation membrane, and a layer of planar guide net. The layers are stacked in the order of long fiber non-woven fabric-short fiber non-woven fabric-PTFE modified separation membrane-planar guide net, and then folded into fins to obtain a folded filter element.
[0079] The prepared filter element was assembled into a cylindrical filter and the same performance characterization as in Example 2 was carried out. During assembly, the folded filter element was wrapped around the circumferential outer surface of the inner support tube of the cylindrical filter structure and fixed, and then an outer support tube was sleeved on the outer surface of the folded filter element. The two sides of the folded filter element were controlled so that the long fiber non-woven fabric was on the upstream side of the fluid flow path, and the planar guide net was on the downstream side of the fluid flow path. The specific characterization results are as follows.
[0080]
[0081] In addition, the antibacterial properties of the PTFE filter element substrate prepared in step (2) and the folded filter element of the PTFE modified separation membrane prepared in step (3) were tested respectively. The oscillation method suitable for contact antibacterial materials was used for the test. Staphylococcus aureus was used as the antibacterial target. The test results showed that the antibacterial rates were 74.6% and 62.2%, respectively.
[0082] From the comparison of the above characterization results with Example 2, it is found that the filter element has a reduced ability to filter metal ions and a reduced effective use accuracy. According to the observation of the invention team, in an ammonia environment, the hydroxyl groups on the surface of tetrafluoroethylene resin can react with hydroxide ions, so that the electrostatic repulsion weakens the probability of tetrafluoroethylene resin particles approaching each other to form precipitation, stabilizes the overall structure of the filter element, and extends its service life. At the same time, chitin in an ammonia solution ensures good anti-settling and anti-sagging capabilities of the resin surface. The researchers infer that the chelating resin in the filter element substrate will form a framework structure composed of metallic aluminum and organic ligands with aluminum triethylphosphate to achieve a continuous sterilization effect. After the organic framework changes, it can induce the production of a large number of oxygen free radicals for sterilization and disinfection.
[0083] Comparative Example 2: A method for preparing a foldable filter element based on a PTFE modified separation membrane. The specific preparation method is the same as Example 2, except that the PTFE base membrane unique to the present invention is changed. An equal amount of tetrafluoroethylene resin is used to replace the chitin fiber, water, and 8-hydroxyquinoline mixture, and acrylamide and initiator treatment are not used to prepare the folded filter element. The specific operations are as follows: (1) Take tetrafluoroethylene resin, heat and stir it to melt it into a fluid, and then put it on the net to form a film. The thickness is controlled to be about 0.6 mm and the flatness is ≤0.1 mm. Let it stand and dry in the shade to obtain the PTFE base membrane.
[0084] (2) The film was stretched at a temperature of 250 °C with a stretching ratio of 200%. After stretching, the two layers of the film were stacked, rolled to a thickness of 1.1 mm, and then hot-pressed at 110 °C to a thickness of 1.0 mm to obtain a PTFE filter element substrate.
[0085] (3) Mix aluminum triethylphosphate and 27% pure ammonia water in a mass ratio of 1:5, and soak the PTFE filter element in the organic solution at 300% volume of the PTFE filter element substrate for 45 minutes.
[0086] (4) The soaked filter element substrate is stacked with a layer of long fiber non-woven fabric, a layer of fine short fiber non-woven fabric, a layer of PTFE modified separation membrane and a layer of planar guide net in sequence to form a filter medium layer. The filter element substrate is stacked in the order of long fiber non-woven fabric-short fiber non-woven fabric-PTFE modified separation membrane-planar guide net, and then folded into fins to obtain a folded filter element.
[0087] The prepared filter element is assembled into a cylindrical filter and then characterized in the same way as in Example 2. During assembly, the folded filter element is wrapped around the circumferential outer surface of the inner support tube of the cylindrical filter structure and fixed, and then an outer support tube is sleeved on the outer surface of the folded filter element. The two sides of the folded filter element are controlled so that the long fiber non-woven fabric is on the upstream side of the fluid flow path, and the planar guide net is on the downstream side of the fluid flow path. The specific characterization results are as follows.
[0088]
[0089] In addition, the antibacterial performance of the PTFE filter element substrate obtained by immersion modification in step (3) and the folded filter element of the PTFE modified separation membrane obtained in step (4) were tested respectively. The test was carried out using an oscillation method suitable for contact antibacterial materials. Staphylococcus aureus was used as the antibacterial target. The test results showed that the antibacterial rates were 96.2% and 75.7%, respectively.
[0090] From the above characterization results and Example 2, it is found that the filter element prepared in the comparative example has a significant decrease in the filtration capacity of metal ions, and the effective service life is also significantly shortened. After observation by the invention team, the PTFE membrane material is extremely hydrophobic. When processing the aqueous phase separation system, the mass transfer driving force of the fluid through the membrane is high, the energy consumption is large, and the water flux is low. The PTFE base membrane provided by the present invention contains a small amount of polyacrylamide, which is evenly arranged in the membrane material, and can be used as a support for the holes in the resin improvement process, providing a spatial structure for the enrichment of metal ions. 8-Hydroxyquinoline can also form 8-hydroxyquinoline chelating resin with special complexing ability, strengthen the adsorption capacity of the base membrane for metal ions, and without corresponding treatment, the inter-membrane restriction effect is enhanced, resulting in a very significant decrease in the actual filtration effect. And from the antibacterial rate results, before stacking and folding, it has relatively good antibacterial properties, but after folding, it is obvious that its antibacterial ability is significantly reduced due to the inter-membrane restriction effect.
[0091] Comparative Example 3: A method for preparing a foldable filter element based on a PTFE modified separation membrane. The specific preparation method is the same as Example 2, except that the PTFE base membrane unique to the present invention is changed. An equal amount of ethylenediaminetetraacetic acid is used instead of 8-hydroxyquinoline to prepare the foldable filter element. The specific operations are as follows: (1) Take tetrafluoroethylene resin, heat and stir to melt it into a fluid, and then put it on the screen to form a film. The thickness is controlled to be about 0.6 mm and the flatness is ≤0.1 mm. During the molding process, after the material temperature drops to 105-115°C, a mixture of chitosan, water, and ethylenediaminetetraacetic acid (50 wt% of the resin mass) is evenly added. The chitosan fiber, water, and ethylenediaminetetraacetic acid mixture are evenly mixed in a ratio of 2:0.5:0.4. At the same time, 7 wt% of acrylamide (7 wt% of the resin mass) and 2 wt% of dibenzoyl oxide (2 wt% of the acrylamide mass) are added. The film is allowed to stand and dry in the shade to obtain a PTFE base membrane.
[0092] (2) The film was stretched at a temperature of 250 °C with a stretching ratio of 200%. After stretching, the two layers of the film were stacked, rolled to a thickness of 1.1 mm, and then hot-pressed at 110 °C to a thickness of 1.0 mm to obtain a PTFE filter element substrate.
[0093] (3) Mix aluminum triethylphosphate and 27% pure ammonia water in a mass ratio of 1:5, and soak the PTFE filter element in the organic solution at 300% volume of the PTFE filter element substrate for 45 minutes.
[0094] (4) The soaked filter element substrate is stacked with a layer of long fiber non-woven fabric, a layer of fine short fiber non-woven fabric, a layer of PTFE modified separation membrane and a layer of planar guide net in sequence to form a filter medium layer. The filter element substrate is stacked in the order of long fiber non-woven fabric-short fiber non-woven fabric-PTFE modified separation membrane-planar guide net, and then folded into fins to obtain a folded filter element.
[0095] The prepared filter element was assembled into a cylindrical filter and then subjected to the same test as in Example 2. During assembly, the folded filter element was wrapped around the circumferential outer surface of the inner support tube of the cylindrical filter structure and fixed, and then an outer support tube was sleeved on the outer surface of the folded filter element. The two sides of the folded filter element were controlled so that the long-fiber non-woven fabric was on the upstream side of the fluid flow path, and the planar guide net was on the downstream side of the fluid flow path. The specific characterization results are as follows.
[0096]
[0097] In addition, the antibacterial performance of the PTFE filter element substrate obtained by immersion modification in step (3) and the folded filter element of the PTFE modified separation membrane obtained in step (4) were tested respectively. The test was carried out using an oscillation method suitable for contact antibacterial materials. Staphylococcus aureus was used as the antibacterial target. The test results showed that the antibacterial rates were 79.6% and 71.2%, respectively.
[0098] By comparing the above characterization results with Example 2, it is found that the filter element prepared in the comparative example has a weaker ability to remove metal ions and also has a longer service life. However, after observation by the invention team, ethylenediaminetetraacetic acid can also form a chelating resin, but EDTA-type chelating resins do not have the ability to slowly release aluminum ions, causing the filter element to lose its bactericidal ability and shortening the service life and actual use effect of the filter element.
[0099] Comparative Example 4: A commercially available polytetrafluoroethylene microporous folded filter element was subjected to the same characterization as in Example 2. The characterization results are shown in the following table.
[0100]
[0101] Analysis of the above characterization results shows that the commercially available polytetrafluoroethylene microporous folded filter element basically has no ability to filter and remove cadmium and has a short service life, but its filtering effect on lead in a short period of time is close to that of the folded filter element prepared by the technical solution of the present invention.
Claims
1. A method for preparing a folded filter element based on a PTFE modified separation membrane, characterized in that: The method comprises: (1) Taking PTFE resin, heating and stirring to melt it into a fluid and then putting it on the screen for molding. During the molding process, when the material temperature drops to 105-115°C, fibers, water, antibacterial agent, acrylamide and initiator are evenly added to obtain a PTFE base film; (2) stretching the PTFE base film, rolling and laminating the multilayer film, and then performing a hot pressing treatment to obtain a PTFE separation membrane; (3) soaking the PTFE separation membrane in an organic solvent to obtain a PTFE modified separation membrane; (4) The soaked PTFE modified separation membrane is sequentially composited and stacked with stacking materials to prepare a folded filter element based on the PTFE modified separation membrane; The fiber in step (1) is chitin fiber; The antibacterial agent in step (1) is 8-hydroxyquinoline; The fiber, water and antibacterial agent in step (1) are mixed in a ratio of 2: (0.3-0.7): (0.2-0.5), and the amount added after mixing is 40-60 wt% of the PTFE value; Step (1) is that the amount of acrylamide added is 5 to 10 wt% of the numerical mass of PTFE; The initiator in step (1) is dibenzoyl peroxide, and the amount added is 1 to 3 wt% of the mass of acrylamide; The organic solvent in step (3) is a mixture of aluminum triethylphosphate and ammonia water, wherein the mass ratio of aluminum triethylphosphate to ammonia water is 1:(4-6), and the amount of organic solvent added is 200-500%VOL of the volume of the PTFE base membrane; The concentration of the aqueous ammonia is 25-28 wt %.
2. The method for preparing a folded filter element based on a PTFE modified separation membrane according to claim 1, characterized in that: The net forming in step (1) is dried to form a film under the conditions of an ambient temperature of 20 to 60°C and an air flow rate of 25 to 30 km / h, and the film thickness is controlled to be 0.5 to 2.0 mm and the flatness is ≤0.1 mm.
3. The method for preparing a folded filter element based on a PTFE modified separation membrane according to claim 1, characterized in that: The stretching in step (2) is to stretch the PTFE base film at 200-300° C., and the stretching ratio is controlled to be 150-300% during the stretching process.
4. The method for preparing a folded filter element based on a PTFE modified separation membrane according to claim 1, characterized in that: In step (2), when the multilayer membranes are rolled and laminated, the total thickness of the multilayer membranes when stacked is controlled to be 115-120% of the target thickness of the PTFE modified separation membrane, and then rolled to 110-115% of the target thickness of the PTFE modified separation membrane; The hot pressing treatment in step (2) is performed at 110-115° C. to heat press the membrane to the target thickness of the PTFE modified separation membrane.
5. The method for preparing a folded filter element based on a PTFE modified separation membrane according to claim 1, characterized in that: The stacked materials in step (4) include long-fiber nonwoven fabric, short-fiber nonwoven fabric and a planar flow guide net; The composite stacking in step (4) is performed in the order of long fiber nonwoven fabric-short fiber nonwoven fabric-PTFE modified separation membrane-planar guide net, and then folded into fins to obtain a folded filter element.
6. A folded filter element based on a PTFE modified separation membrane prepared by the method of any one of claims 1 to 5.
7. A foldable filter element based on PTFE modified separation membrane according to claim 6, characterized in that: The folded filter element is wrapped around the circumferential outer surface of the inner support cylinder of the cylindrical filter structure and fixed, and then the outer support cylinder is sleeved on the outer surface of the folded filter element; The two sides of the folded filter element are controlled so that the long-fiber non-woven fabric is located on the upstream side of the fluid flow path, and the planar flow guide net is located on the downstream side of the fluid flow path.
Citation Information
Patent Citations
Hydrophilic polyfluortetraethylene microporous membrane folding type filter element
CN101590336A
Preparation method of diaphragm for alkaline electrolyzed water
CN116791144A
Composite diaphragm material and preparation method thereof
CN116885384A